Development of the capacity to suffer in embryos and chicks: a systematic review of relevant studies - Mace, Jenny L.; Knight, Andrew (Frontiers in Veterinary Science, 2025)
Approximately 1.8 billion chicks are hatched worldwide in commercial hatcheries every month. A typical commercial hatchery is a high-speed and stressful environment. Not only is chick welfare impacted while at the hatchery, but also chickens’ early life experiences can have long-lasting impacts on their welfare once they leave the hatcheries. Additionally, chick embryos may have the capacity to experience stress and pain. This study systematically reviewed recent scientific studies exploring the starting point for the capacity to suffer in chicks and chick embryos. It found that the capacity to suffer (i.e., to experience pain, distress, or other prolonged negative welfare states) may commence by embryonic day 18—three days before hatching—and likely earlier. Based on this, serious and widespread welfare problems may exist for the 1.8 billion chicks hatched in hatcheries globally every month.